Self-Regulated Learning Interventions With at-Risk Youth: Enhancing Adaptability, Performance, and Well-Being.
DOI: 10.1037/14641-003
|View full text |Cite
|
Sign up to set email alerts
|

Self-management interventions to reduce disruptive classroom behavior.

Abstract: Calling out, engaging in side conversations with peers, getting out of one's seat, playing with objects-although common to many classroom settings, these types of disruptions can significantly interfere with the learning of the students involved and their larger community of peers (Walker et al., 1994). A 1995 poll conducted by the American Federation of Teachers found that 17% of classroom teachers reported losing 4 or more hours of instructional time each week due to disruptive behavior (Walker, Ramsey, & G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(2 citation statements)
references
References 48 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Prior research has shown discipline referrals to be related to a wide range of behavioral issues, including disruptive behaviors, social skills deficits, poor behavioral control, and school dropout (Pas, Bradshaw, & Mitchell, ). Given that deficient self‐regulatory skills are often linked with many of these behavioral problems (Barkley, ; Briesch & Briesch, ), we anticipated that the SRSI‐SR would exhibit significant relations to office disciplinary referrals. More specifically, we expected to observe negative relations between discipline referrals and the two adaptive self‐report subscales and positive relations between discipline referrals and the maladaptive regulatory subscale.…”
Section: Rationale and Primary Objectivesmentioning
confidence: 99%
“…Prior research has shown discipline referrals to be related to a wide range of behavioral issues, including disruptive behaviors, social skills deficits, poor behavioral control, and school dropout (Pas, Bradshaw, & Mitchell, ). Given that deficient self‐regulatory skills are often linked with many of these behavioral problems (Barkley, ; Briesch & Briesch, ), we anticipated that the SRSI‐SR would exhibit significant relations to office disciplinary referrals. More specifically, we expected to observe negative relations between discipline referrals and the two adaptive self‐report subscales and positive relations between discipline referrals and the maladaptive regulatory subscale.…”
Section: Rationale and Primary Objectivesmentioning
confidence: 99%
“…The individual then administers self‐reinforcement depending on the result of this evaluation (e.g., delivering positive self‐statements for meeting a goal, restricting rewards for not meeting a goal). Because Kanfer's theory was generated through research with adults, the extent to which cognitive processes are similar among children remains unclear (Briesch & Briesch, ). Given children's limited metacognition, setting individual goals, conducting reflective evaluations, and providing behavioral feedback within discussions with an adult may help to scaffold developing self‐evaluation processes, and ensure that the self‐evaluation and self‐reinforcement phases of Kanfer's theory actually occur.…”
mentioning
confidence: 99%